2019
DOI: 10.1104/pp.19.01009
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Pathway: FLOWERING LOCUS C Repression through an Antisense-Mediated Chromatin-Silencing Mechanism

Abstract: The timing of flowering is vital for plant reproductive success and is therefore tightly regulated by endogenous and exogenous cues. In summer annual Arabidopsis (Arabidopsis thaliana) accessions, like Columbia-0, rapid flowering is promoted by repression of the floral repressor FLOWERING LOCUS C (FLC). This is through the activity of the autonomous pathway, a group of proteins with diverse functions including RNA 39-end processing factors, spliceosome components, a transcription elongation factor, and chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 112 publications
0
75
0
Order By: Relevance
“…Previous researchers have reported that cis -NATs regulate plant temperature response 52 , 53 . In addition, pri-miR398b, pri-miR398c and mature miR398 are induced by heat stress in Arabidopsis 42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researchers have reported that cis -NATs regulate plant temperature response 52 , 53 . In addition, pri-miR398b, pri-miR398c and mature miR398 are induced by heat stress in Arabidopsis 42 .…”
Section: Resultsmentioning
confidence: 99%
“…The expression of noncoding RNAs that transcribe in the opposite direction of protein-coding genes is often positively or negatively correlated with their cognate sense genes 31 , 52 , 53 . The cold-induced antisense transcript COOLAIR represses FLOWERING LOCUS C ( FLC ) transcription with increased H3K27me3 and decreased H3K36me3 levels in response to cold temperatures 52 , 66 . And the cold-induced antisense transcript SVALKA-asCBF1 suppresses CBF1 by RNAPII collision stemming 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Enod40 was found to trigger changes in subcellular localization of the nuclear RNA binding protein MtRBP1 (Crespi et al 1994 ; Campalans et al 2004 ). Since then, plant lncRNAs have been identified as regulators of miRNA activity (Franco-Zorrilla et al 2007 ), epigenetic regulation (Swiezewski et al 2009 ; Wu et al 2020 ) and modulation of chromatin structure (Ariel et al 2014 , 2020 ; Kim and Sung 2018 ). Furthermore, the two antisense lncRNAs LAIR ( LRK Antisense Intergenic RNA ) and MAS (MAF4 antisense RNA) were found to interact with WDR5 (a component of the COMPASS-like complex) thereby regulating flowering time in rice and Arabidopsis, respectively (Wang et al 2018 ; Zhao et al 2018 ).…”
Section: Discovery and Classification Of Lncrnasmentioning
confidence: 99%
“…Proximal poly(A) site selection requires components of the cleavage and polyadenylation machinery, including the nucleuslocalized RNA-binding protein FCA that is necessary for 39-end processing. The Update by Wu et al (2020) is an excellent primer on the factors involved in FLC regulation that have been identified in screens for suppressors of overexpressed FCA. These mutants uncover machinery necessary for polyadenylation, splicing, transcriptional elongation, and histone modification.…”
Section: Histone Modifications and 39-end Processingmentioning
confidence: 99%